2019
DOI: 10.1167/iovs.18-25967
|View full text |Cite
|
Sign up to set email alerts
|

IMI – Report on Experimental Models of Emmetropization and Myopia

Abstract: The results of many studies in a variety of species have significantly advanced our understanding of the role of visual experience and the mechanisms of postnatal eye growth, and the development of myopia. This paper surveys and reviews the major contributions that experimental studies using animal models have made to our thinking about emmetropization and development of myopia. These studies established important concepts informing our knowledge of the visual regulation of eye growth and refractive developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
304
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(320 citation statements)
references
References 728 publications
(1,321 reference statements)
9
304
1
6
Order By: Relevance
“…Studies also use lenses to alter the image plane with respect to the retina, resulting in image defocus that induces compensatory alterations in ocular growth, known as lens‐induced myopia or hyperopia . Both form‐deprivation and lens‐induced defocus result in abnormal eye growth and refractive error development, with associated anatomical, optical, and biochemical changes in the anterior and posterior segments of the eye (see inclusive reviews) . In this section, we will define the process of emmetropisation, summarise different optical aspects of FDM and lens‐induced ametropias, including their similarities and differences, and describe how these experimental models have informed us about refractive error development in humans.…”
Section: Optical Defocus and Visual Regulation Of Ocular Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies also use lenses to alter the image plane with respect to the retina, resulting in image defocus that induces compensatory alterations in ocular growth, known as lens‐induced myopia or hyperopia . Both form‐deprivation and lens‐induced defocus result in abnormal eye growth and refractive error development, with associated anatomical, optical, and biochemical changes in the anterior and posterior segments of the eye (see inclusive reviews) . In this section, we will define the process of emmetropisation, summarise different optical aspects of FDM and lens‐induced ametropias, including their similarities and differences, and describe how these experimental models have informed us about refractive error development in humans.…”
Section: Optical Defocus and Visual Regulation Of Ocular Growthmentioning
confidence: 99%
“…As shown in Figure , a large part of our current knowledge of visual regulation of ocular growth has originated from experimental studies describing the ability of the eye to compensate for myopic or hyperopic defocus, imposed with positive or negative lenses, respectively. When defocus is induced, the eye undergoes compensatory changes in ocular growth to match its axial length to the altered focal plane, thereby decreasing or eliminating the imposed refractive error . Myopic defocus induced with positive lenses leads to a thickening of the choroid which brings the retina forward, a slowing of axial elongation, and a hyperopic shift in refraction.…”
Section: Optical Defocus and Visual Regulation Of Ocular Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the dominant role of the peripheral retina in this regard is likely due to spatial summation and the greater absolute number of neurons in the peripheral versus central retina . Although the way in which local sign of defocus is computed from the retinal image is not understood, it is generally held that it is the sign of the spherical component of defocus which determines the eye growth signal, with myopic defocus slowing eye growth and hyperopic defocus accelerating it …”
Section: Introductionmentioning
confidence: 99%
“…The rationale for prescribing under‐correction for myopia is to bring the image shell in front of the retina to present a retarding blur stimulus based on findings from animal studies . It is also considered to be an attempt to reduce the accommodative stimulus and demand at near and thus reduce the blur that drives accommodation .…”
mentioning
confidence: 99%